Sistemas de Administración de Anestesia Local Controlada por Ordenador - Yacelga Mejía, Luis Alexander (2024)
The administration of local anesthesia is crucial in dental practice to control patient pain and anxiety, especially in invasive procedures. Traditionally, anesthesia is administered using conventional syringes, causing variability in the dose and speed of administration due to manual control. However, developing computer-controlled local anesthesia delivery (CCLAD) systems improves this process significantly. It reduces the risk of tissue damage and strain associated with traditional techniques. This study conducted a systematic review following the PRISMA method, focused on evaluating the effectiveness of CCLAD compared to conventional methods using high-impact scientific databases. The results of this review indicated that CCLAD tends to be preferred by patients and professionals due to its ability to deliver anesthesia more efficiently and with less pain. Furthermore, they showed that patients treated with CCLAD experienced lower pain intensity and anxiety. They were evaluated using the Visual Analogue Scale (VAS) and the Wong-Baker FACES Pain Rating Scale. Likewise, advantages were observed regarding physiological parameters, such as a more stable heart rate and reduced cortisol levels. In conclusion, CCLAD improves the patient experience by reducing pain and anxiety. The findings also support the implementation of this System as a standard for the administration of anesthesia in dentistry, considering the individual needs of the patients and the specificity of the procedures to be performed.